Dimensi Carter Kualitas Layanan Bank Syariah Indonesia: Studi Komparatif Sebelum dan Setelah Merger - Dian Sugiarti; Any Meilani (ITB AAS INDONESIA Surakarta, 2021)
Islamic banking in Indonesia recorded a new history with the merger of three Islamic banks, namely Bank Syariah Mandiri, BNI Syariah and BRI Syariah. There are concerns arising from customers of the three Islamic banks of the merger in the transition period of bank merger. This customer concern, making Bank Syariah Indonesia try to provide the best value for consumers. This makes quality an important part of Bank Syariah Indonesia in carrying out its operational strategy to lure customers in assessing its performance. To find out how much service quality a bank, it can use an analysis in a dimension one of which is the DIMENSION OF CARTER (Compliance, Assurance, Reliability, Tangibility, Emphaty, Responsiveness) as a form of modification of SERVQUAL to be suitable for measuring the quality of islamic bank services. This study is a multiyear study that will be conducted within a period of 2 years and aims to compare the quality of services of Bank Syariah Indonesia before and after the merger. This research is a quantitative study study in comparison with kohrt survey. Data collection methods are done by collecting primary and secondary data. Primary data is obtained through the dissemination of questionnaires. Secondary data is obtained through literature studies by studying the results of studies and relevant document documents. Respondents in this study were customers of Bank Syariah Indonesia with predetermined characteristics. The study used a sign test or wilcoxon to analyze the data. This research is expected to have significant implications for both the theory and policy of state-owned Islamic Banks in improving the quality of their services in order to reach a wider market share. This research has targets and external in the form of national journals.